PENGARUH INDEPENDENSI, KOMPETENSI, DAN INTEGRITAS TERHADAP PEMBERIAN OPINI AUDIT (Studi Kasus pada Inspektorat Provinsi Bengkulu) - Sianturi Duma Roland; Nina Yulianasari (Universitas Prof.Hazairin,SH Bengkulu, 2019)
This study discusses the importance of independence, competence, and integration in giving audit opinions in the Bengkulu Province Inspectorate. Methods of data analysis using Multiple Linear Regression. From the Calculation Result, a linear regression equation is obtained, namely Y = 3,410 + 0,281X1 + 0,523X2 + 0,114X3 + ?, where from the results which can be interpreted, a positive relationship between the two variables is needed. The coefficient of determination (R ²) of 0.827 shows the effect of independence, competence, and integrity on the provision of audit opinions in the Inspectorate of Bengkulu Province is very strong. Based on the t value obtained in the hypothesis test (t-test), then the t value obtained is 2.771 for the first variable, t arithmetic for 5.530 for the first variable, t arithmetic for 2.245 for the variable variable, while the t table value is 1.683 (t arithmetic )> t table). This means that the hypothesis is accepted or below the value of 0.05, proving independence, competence, and positive integrity of the audit opinion in the Bengkulu Province Inspectorate.